2023
DOI: 10.3390/su151813283
|View full text |Cite
|
Sign up to set email alerts
|

Giant Trevally Optimization Approach for Probabilistic Optimal Power Flow of Power Systems Including Renewable Energy Systems Uncertainty

Mohamed S. Hashish,
Hany M. Hasanien,
Zia Ullah
et al.

Abstract: In this study, the Giant Trevally Optimizer (GTO) is employed to solve the probabilistic optimum power flow (P-OPF) issue, considering Renewable Energy Source (RES) uncertainties, achieving notable cost reduction. The objective function is established to minimize the overall generation cost, including the RES cost, which significantly surpassing existing solutions. The uncertain nature of the RES is represented through the employment of a Monte Carlo Simulation (MCS), strengthened by the K-means Clustering app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Finally, adding fractional operators and stochastic white noise results in more realistic I-V curves tangible to the actual datasheet curves. Future works will introduce the application of the proposed PV modeling in power systems [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, adding fractional operators and stochastic white noise results in more realistic I-V curves tangible to the actual datasheet curves. Future works will introduce the application of the proposed PV modeling in power systems [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The mode of operation of the gas boiler can be modeled as (15) where P g GB (t) is the natural gas power input into the gas boiler in time period t; P h GB (t) is the thermal energy output from the gas boiler in time period t; R h GB is the thermal energy conversion rate of the gas boiler; P g,max GB and P g,min GB are the upper and lower limits of the natural gas power input into the gas boiler, respectively; and ∆P g,max GB and ∆P g,min GB are the upper and lower limits of the creep of the gas boiler, respectively.…”
Section: Integrated Energy Station Planning Model With Carbon Capture...mentioning
confidence: 99%
“…References [13,14] analyzed the accuracy of Monte Carlo methods based on specific scenarios. References [15,16] considered the correlation between wind farms that are close together when analyzing the probabilistic power flow operation characteristics of power systems. Reference [17] illustrated that the semi-invariant method can be used to effectively resolve the probability distribution of different state quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results showed that BPNN outperformed conventional algorithms in terms of speed. Apart from ANNs, there are various ML algorithms indirectly used for solving the OPF problem, such as support vector machine (SVM) [34,35], random forest [36,37], K-means [38,39], and others.…”
Section: Introductionmentioning
confidence: 99%